2023
DOI: 10.3417/2023815
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Matelea (Apocynaceae, Gonolobinae) from Bolivia and an Assessment of Matelea in Bolivia

Abstract: Matelea anomala Morillo, Meve & Liede (Apocynaceae, Asclepiadeae, Gonolobinae) is here described and illustrated. The new taxon, known only from a single locality in eastern central Bolivia, is characterized by very small flowers with a campanulate corolla and recurved, abaxially pubescent and not ocellate corolla lobes, an annular corona with fimbriate-crenulate margins, and a terete stipe carrying the gynostegium. The new species is recognized in Matelea Aubl. s. str., for which a generic description is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
1
0
0
5
Order By: Relevance
“…(Alvarado-Cárdenas and Cortez, 2022), or established new genera (Morillo, 2012(Morillo, , 2013(Morillo, , 2015(Morillo, , 2016(Morillo, , 2023aMorillo et al, 2013Mangelsdorff et al, 2016;Keller and Liede-Schumann, 2020;Alvarado-Cárdenas, 2021). It has been suggested that Matelea s.s. (sensu Krings and Morillo, 2015;Morillo, 2015;Morillo et al, 2017Morillo et al, , 2023 only contains around 20 species, morphologically consistent with the type species M. palustris Aubl. (Stevens, 2001;Krings and Morillo, 2015).…”
Section: Introductionsupporting
confidence: 54%
“…(Alvarado-Cárdenas and Cortez, 2022), or established new genera (Morillo, 2012(Morillo, , 2013(Morillo, , 2015(Morillo, , 2016(Morillo, , 2023aMorillo et al, 2013Mangelsdorff et al, 2016;Keller and Liede-Schumann, 2020;Alvarado-Cárdenas, 2021). It has been suggested that Matelea s.s. (sensu Krings and Morillo, 2015;Morillo, 2015;Morillo et al, 2017Morillo et al, , 2023 only contains around 20 species, morphologically consistent with the type species M. palustris Aubl. (Stevens, 2001;Krings and Morillo, 2015).…”
Section: Introductionsupporting
confidence: 54%
“…Si bien el género Matelea aún requiere atención en la delimitación de sus especies, la propuesta de Morillo et al (2023) es un buen referente para el desarrollo de esta circunscripción y en la cual nos basamos para esta descripción.…”
Section: Discussionunclassified
“…Matelea lilliputiana es morfológicamente similar a M. anomala, ya que ambas tienen corolas pequeñas (menos de 5 mm de largo) y blanquecinas, corona ginostegial discoide y con el ginostegio exserto (Morillo 2023). Los individuos de la nueva especie se distinguen porque presentan una corona ginostegial 5-lobada, cuyos lóbulos tienen un ápice bilobado (vs. corona ginostegial poco diferenciada en 5-lóbulos y con margen fimbriado en M. anomala), el estípite es anguloso (vs. cilíndrico) y las anteras tienen una base aguda y pronunciada (vs. base truncada).…”
Section: Discussionunclassified
See 2 more Smart Citations